A Synthesis of Spirocyclic Oxazinoisoquinolines and Oxazinoquinolines Bearing Thiazolopyrimidine Moieties - Yavari, Issa; Hojati, Mahniya; Azad, Leila; Halvagar, Mohammad R. (Synlett, 2018)
The reaction of isoquinoline or quinoline with dialkyl acetylenedicarboxylates in the presence of alkyl 2-{3,5-dioxo-5H-thiazolo[3,2-a]pyrimidin-2(3H)-ylidene}acetates (generated in situ from acetylenedicarboxylates and 2-thiouracils) led to dialkyl 2-(2-alkoxy-2-oxoethylidene)-5-oxo-2H,5H,11b′H-spiro{thiazolo[3,2-a]pyrimidine-3,2′-[1,3]oxazino[2,3-a]isoquinoline}-3′,4′-dicarboxylates or dialkyl 2-(2-alkoxy-2-oxoethylidene)-5-oxo-2H,4a′H,5H-spiro{thiazolo[3,2-a]pyrimidine-3,2′-[1,3]oxazino[3,2-a]quinoline}-1′,2′-dicarboxylates in good yields. The structure of the target compounds was confirmed by X-ray diffraction study.
Keywords: Huisgen’s 1,4-dipole; N-heterocycles; acetylenic esters; spiro compounds; thiouracil